Effect of swimming exercise program on quality of life in patients with diabetic foot ulcer - Alzghou, Obada Twffeg; Aman, Rahimi Che (Edelweiss Applied Science and Technology, 2024)
This research aimed to examine the effect of a swimming exercise program on the quality of life in patients with diabetic foot ulcers (DFUs). DFUs are a common complication of diabetes that significantly impact patients' physical and psychological well-being and impose a substantial burden on healthcare systems. Physical activity, including swimming, has been shown to improve various aspects of health and well-being. However, its specific effects on the quality of life in patients with DFUs have not been extensively studied. The study included twenty patients diagnosed with DFUs who volunteered to participate in a 12-week swimming exercise program. The program consisted of three one-hour sessions per week, with exercises performed in an indoor swimming pool. Participants' quality of life was assessed using the Diabetic Foot Ulcer Scale Short Form (DFS-SF) before the program and at 4, 8, and 12 weeks into the program. The results demonstrated significant improvements in various domains of quality of life among participants. The leisure, physical health, dependence/daily life, negative emotions, worry about ulcers/feet, and bothered by ulcer care domains all showed positive changes, with reduced scores on negative items and increased scores on positive items over time. These findings highlight the potential benefits of swimming as a therapeutic intervention for improving the quality of life in patients with DFUs. Swimming, as a low-impact aerobic exercise, offers physiological and psychological advantages, including fat burning, mood improvement, stress reduction, and enhanced cognitive function. The study suggests that incorporating swimming exercise programs into the management and treatment of DFUs may lead to improved overall well-being and quality of life for these patients. Further research and larger-scale studies are necessary to validate these findings and explore the long-term effects of swimming exercise programs on the quality of life in patients with DFUs. Nevertheless, this research provides valuable insights for healthcare professionals in developing comprehensive treatment approaches for individuals with DFUs.